Pengaruh islamic human development index dan pertumbuhan ekonomi terhadap kemiskinan dengan pengangguran sebagai variabel intervening - Aiu Viollani, Kity; Siswanto, Siswanto; Suprayitno , Eko (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Poverty is no longer a foreign problem to be discussed, moreover this problem has become an international problem, including Indonesia. This problem was exacerbated by the outbreak of the deadly disease Covid-19 which caused the Indonesian economy to slump further, not least from the economic sector that went out of business and high layoffs occurred. Many efforts must be made to reduce poverty, such as increasing human resource development, increasing economic growth and reducing unemployment. This study aims to determine the effect of the Islamic Human Development Index and economic growth on poverty with unemployment as an intervening variable in Indonesia in 2016-2020. This study uses quantitative research methods, and path testing as an analytical tool. The data used is panel data from 34 provinces spread across Indonesia with a total observation of 136 samples. The direct test results show that I-HDI and economic growth have a significant negative effect on unemployment, while the indirect test results show that I-HDI and economic growth have a significant negative effect on poverty, while the unemployment variable can mediate the I-HDI relationship on poverty and economic growth. against poverty.